2001
DOI: 10.1007/bf03016592
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplanchnic oxygenation is better preserved during mild hypothermic than during normothermic cardiopulmonary bypass

Abstract: P Pu ur rp po os se e: : To assess and compare the effects of normothermic and mild hypothermic cardiopulmonary bypass (CPB) on hepatosplanchnic oxygenation.M Me et th ho od ds s: : We studied 14 patients scheduled for elective coronary artery bypass graft surgery who underwent normothermic (>35°C; group I, n=7) or mild hypothermic (32°C; group II, n=7) CPB. After induction of anesthesia, a hepatic venous catheter was inserted into the right hepatic vein to monitor hepatic venous oxygen saturation (ShvO 2 ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Also, the hepatic blood flow, as assessed by indocyanine green method, did not change during cardiac surgery when performed under the same anaesthetic condition and normothermic CPB management as used in this study. 18 Propofol binds mostly to albumin and to erythrocyte membrane. 7 The increase in the unbound fraction was probably caused by a lower concentration of albumin and haematocrit as a result of the sudden haemodilution (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the hepatic blood flow, as assessed by indocyanine green method, did not change during cardiac surgery when performed under the same anaesthetic condition and normothermic CPB management as used in this study. 18 Propofol binds mostly to albumin and to erythrocyte membrane. 7 The increase in the unbound fraction was probably caused by a lower concentration of albumin and haematocrit as a result of the sudden haemodilution (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that hypoxia or tissue hypoxygenation increases AM mRNA expression in a human colorectal carcinoma cell line; in primary cultures of rat ventricular myocytes (11,12); and in the brain, liver, lung, kidney, and heart (13). We have reported that oxygen consumption exceeds oxygen delivery specifically in the hepatosplanchnic region during normothermic CPB, resulting in a marked reduction in Shvo 2 (16). In this study, the oxygen tension in the hepatic vein selectively decreased during CPB.…”
Section: Discussionmentioning
confidence: 42%
“…We have previously reported that oxygen consumption exceeds oxygen delivery in the hepatosplanchnic circulation during normothermic CPB (16). Specifically, the hepatic venous oxygen saturation (Shvo 2 ) decreases from the baseline value 10 and 60 min after the onset of CPB.…”
mentioning
confidence: 96%
“…Temperature, bypass mode, and bypass flow may at least in part explain these discrepancies. Increased hepatosplanchnic oxygen consumption and oxygen extraction have been reported during normothermic CPB by some (35,36) but not all (33) authors. In the present study, only a partial extracorporeal circuit without an oxygenator was used; hence, our model may not reflect all the pathophysiologic features of CPB.…”
Section: Discussionmentioning
confidence: 95%